Mereduksi Voice of Customer pada Pengembangan Produk Alat Pembuka Tutup Galon Menggunakan Analisis Faktor - Glisina Dwinoor Rembulan; Tony Wijaya; Andrew Ruslie; Jordy Jordy; Rama Adi Saputra Sunadynatha (Universitas Bunda Mulia, 2020)
Currently, bottled drinking water has become the main choice for Indonesians. The percentage of consumption of bottled drinking water by Indonesians in 2018 reached 36.28% and an increase in 2019 reached 38.25%. One package that is often used is gallon packaging. There are several problems that people find when opening the gallon lid. The results of initial interviews with the community indicated that there were several problems, including the high risk of injury to the hands if you opened the gallon lid using a knife and the hands hurt if you opened the gallon cap manually without tools. These problems can be overcome by developing a product for a gallon cap opener that is tailored to customer needs or voice of customer (VOC). The method used in this research is factor analysis. A large number of community necessities make the product development process difficult because of the many needs that must be met. The purpose of this study was to reduce the number of VOCs. The Kaiser Meyer Olkin (KMO) test was used to see the suitability of the data used in factor analysis, while Bartlett's test was used to determine the significant correlation on each indicator. The result of factor analysis shows that 12 customer needs can be reduced to 3 customer needs, namely affordable gallon cap opening price, adjustable gallon cap opener diameter, and multifunctional gallon lid opener.